Efficacite Du Baume De Cajou Contre Les Chenilles Carpophages Du Cotonnier Au Nord Du Benin - Saturnin Azonkpin; Daniel Chèpo Chougourou; Aimé H. Bokonon-Ganta; Joseph Dossou; Léonard E. Ahoton; Mohamed M. Soumanou; Simplice D. Vodouhe (European Scientific Journal, ESJ, 2018)
Cotton remains the main source of foreign exchange for Benin. This study aims to contribute to increased yield of organic cotton through the evaluation of the effectiveness of cashew balm as an alternative method of management of carpophagous pests of cotton. The experimental setup consists of Fisher Blocks with 6 objects in 4 repetitions. The objects compared are '' Unprocessed '', the Agri-bio-pesticide dosed at 1 l / ha, two concentrations (1% and 2%) of the hot and cold-extracted cashew balm. Linear mixed or fixed effects models and generalized linear models with mixed or fixed effects were used to determine the influence of the objects on the carpophagous larva and their damage in 2015 and 2016 in Thya to the north of Benin. The number of Helicoverpa armigera larva found in 30 plants ranged from 1.2 (Agri-biopesticide) to 2.3 (Untreated) in 2015. The percentages of green capsules with holes varied by 36.08% (Agri-bio-pesticide) at 53.68% (1% cold-extracted balm) in 2015. The percentages of ripe capsules with holes varied from 32.05% (hot-pressed balm at 2%) to 45.00% (Untreated) in 2016. Seed cotton yield ranged from 229.91 kg / ha (Untreated) to 500 kg / ha (Agri-biopesticide) in 2016. It is noted that Agri-bio-pesticide and the 2% dose of cashew balm, were more effective than that of 1%. The cashew balm is positioned as an alternative to biopesticides used in organic cotton farming.